Catalytic asymmetric total synthesis of diazabicyclooctane β-lactamase inhibitors avibactam and relebactam. Issue 77 (8th September 2022) - Yang, Zhi; Chen, Yu; Wan, Linxi; Cen, Xiangling; Tang, Pei; Chen, Fener
Abstract : The first catalytic asymmetric total synthesis of marketed DBO β-lactamase inhibitors avibactam and relebactam has been achieved via a Rh-catalysed asymmetric hydrogenation along with multiple flow procedures. Abstract : A catalytic asymmetric total synthesis of avibactam and relebactam, two marketed diazabicyclooctane (DBO) β-lactamase inhibitors (BLIs), has been accomplished. An important feature of this study is the creation of a stereogenic center by using Rh-catalysed asymmetric hydrogenation, affording the crucial α-amino acid ester derivative with high-level enantiocontrol (99% ee). Furthermore, the adoption of flow technologies for the assembly of a majority of intermediates significantly achieves a faster preparation and greater synthetic efficiency than corresponding batch procedures.